Blood markers in remote ischaemic conditioning for acute ischaemic stroke: data from the REmote ischaemic Conditioning After Stroke Trial. (14th December 2020) - Appleton, Jason P.; O'Sullivan, Saoirse E.; Hedstrom, Amanda; May, Jane A.; Donnelly, Richard; Sprigg, Nikola; Bath, Philip M.; England, Timothy J.
Abstract: Background and purpose: Remote ischaemic per‐conditioning (RIC) is neuroprotective in experimental ischaemic stroke. Several neurohumoral, vascular and inflammatory mediators are implicated. The effect of RIC on plasma biomarkers was assessed using clinical data from the REmote ischaemic Conditioning After Stroke Trial (RECAST‐1). Methods: RECAST‐1 was a pilot sham‐controlled blinded trial in 26 patients with ischaemic stroke, randomized to receive four 5‐min cycles of RIC within 24 h of ictus. Plasma taken pre‐intervention, immediately post‐intervention and on day 4 was analysed for nitric oxide (nitrate/nitrite) using chemiluminescence and all other biomarkers by multiplex analysis. Biomarkers were correlated with clinical outcome (day 90 National Institutes of Health Stroke Scale, modified Rankin Scale, Barthel index). Results: Remote ischaemic per‐conditioning reduced serum amyloid protein (SAP) and tissue necrosis factor α (TNF‐α) levels from pre‐ to post‐intervention ( n  = 13, two‐way ANOVA, p  < 0.05). Overall ( n  = 26), increases in SAP pre‐ to post‐intervention and pre‐intervention to day 4 were moderately correlated with worse day 90 clinical outcomes. No consistent significant changes over time, or by treatment, or correlations with outcome were seen for other biomarkers. Conclusions: Remote ischaemic per‐conditioning reduced SAP and TNF‐α levels from pre‐ to post‐intervention. Increases in plasma levels of SAP were associated with worse clinical outcomes after ischaemic stroke. Larger studies assessing biomarkers and the safety and efficacy of RIC in acute ischaemic stroke are warranted to further understand these relationships. Abstract : Remote ischaemic conditioning (RIC) reduces serum amyloid protein and tissue necrosis factor α in acute ischaemic stroke. Larger studies assessing biomarkers and the safety and efficacy of RIC in acute ischaemic stroke are needed.